Effect of pore size distribution index on permeability - Chen, Chin-chung; Arbhabhirama Anat; Kinori, Ben-Zion; Subin Pinkayan; Asian Institute of Technology (Bangkok, Thailand : Asian Institute of Technology, 1973)
It is desirable from many points of view to know quantitatively how the permeability of a porous medium is related to its complex geometry or texture of the pore spaces. This investigation considers a coefficient describing the pore size distribution of a medium and its effect on permeability. An equation was developed relating the permeability with porosity, characteristic grain size diameter and a constant which is a function of the pore size distribution index of the medium. Experiments .were conducted to determine the functional relationship of the constant and the pore size distribution index. The media selected had a wide range of texture, porosity and pore size distribution. The wetting fluid used was distilled water and the nonwetting fluid was air.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering at the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1973
Keywords: Permeability; Soil permeability; Seepage